Longitudinal variation of equatorial electrojet and the occurrence of its counter electrojet - A. B. Rabiu; O. O. Folarin; O. O. Folarin; T. Uozumi; N. S. Abdul Hamid; A. Yoshikawa (Annales Geophysicae, 2017)
We examined the longitudinal variability of the equatorial electrojet (EEJ) and the occurrence of its counter electrojet (CEJ) using the available records of the horizontal component H of the geomagnetic field simultaneously recorded in the year 2009 (mean annual sunspot number Rz  =  3.1) along the magnetic equator in the South American, African, and Philippine sectors. Our results indicate that the EEJ undergoes variability from one longitudinal representative station to another, with the strongest EEJ of about 192.5 nT at the South American axis at Huancayo and a minimum peak of 40.7 nT at Ilorin in western Africa. Obtained longitudinal inequality in the EEJ was explicable in terms of the effects of local winds, dynamics of migratory tides, propagating diurnal tide, and meridional winds. The African stations of Ilorin and Addis Ababa registered the greatest % of CEJ occurrence. Huancayo in South America, with the strongest electrojet strength, was found to have the least occurrence of the CEJ. It is suggested that activities that support strong EEJ inhibits the occurrence of the CEJ. Percentage of occurrence of the CEJ varied with seasons across the longitudes. The order of seasonal variation of morning occurrence does not tally with the evening occurrence order at any station. A semiannual equinoctial maximum in percentage of morning occurrence of the CEJ was obtained at Huancayo and Addis Ababa. Only Addis Ababa recorded equal equinoctial maxima in percentage of evening occurrence of the CEJ. The seasonal distribution of the occurrences of the CEJ at different time regimes implies a seasonal variability of causative mechanisms responsible for the occurrence of the CEJ.